General Aspects of some Causes of Web Application Vulnerabilities - Mironela Pîrnău (Memoirs of the Scientific Sections of the Romanian Academy, 2015)
Because web applications are complex software systems in constant evolution, they become real targets for hackers as they provide direct access to corporate or personal data. Web application security is supposed to represent an essential priority for organizations in order to protect sensitive customer data, or those of the employees of a company. Worldwide, there are many organizations that report the most common types of attacks on Web applications and methods for their prevention. While the paper is an overview, it puts forward several typical examples of web application vulnerabilities that are due to programming errors; these may be used by attackers to take unauthorized control over computers.